2013
DOI: 10.1002/polb.23347
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced phase separation of poly(vinylidene fluoride)/diluent systems: Optical microscope and infrared spectroscopy studies

Abstract: Thermally induced phase separation (TIPS) has been developed to prepare porous membranes. The porous structures are mainly dependent on diluents adopted in the TIPS process. We obtained two typical morphologies of poly(vinylidene fluoride) (PVDF) membranes using cyclohexanone (CO) and propylene carbonate (PC) as diluents, respectively. SEM observation displays that porous spherulites are formed from PVDF/CO system, whereas smooth particles result from PVDF/PC system. The TIPS processes of these two systems hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…As diluent is closely related to phase separation, different diluent cause different pore structures [77]. The advantages of this method are simplicity of the process, high reproducibility, low defects rate, high porosity and narrow pore size distribution [78].…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…As diluent is closely related to phase separation, different diluent cause different pore structures [77]. The advantages of this method are simplicity of the process, high reproducibility, low defects rate, high porosity and narrow pore size distribution [78].…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…22,23 At the same time appear bands at 841 and 1275 cm À1 , characteristic for b-phase. 22,23 Moreover, the bands at 613, 762, 874 and 1275 cm À1 were attributed to the CCC skeletal bending vibration. The characteristic bands at 874, 1071 and 1275 cm À1 were assigned to the CC skeletal symmetric stretching vibration, while the bands at 841, 874, 1177 and 1275 cm À1 were assigned to the CF 2 symmetric stretching vibration.…”
Section: Resultsmentioning
confidence: 86%
“…7,21 The characteristic bands of a-phase were observed at 613, 762, 797, 874, 976, 1071, 1177 and 1398 cm À1 . [22][23][24] The band at 841 cm À1 , assigned to the gphase. 22,23 At the same time appear bands at 841 and 1275 cm À1 , characteristic for b-phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bands at 615, 766, 795, 874, 974, 1070, 1148, 1182, 1210, 1383, 1402, 1432 and 1455 cm −1 can be associated to α-phase, whereas bands at 840, 882 and 1275 cm −1 are fingerprints of β-phase. 14,1618 Interestingly, a small signal at 1235 cm −1 corresponding to γ-phase is also detected. From these results, it can be concluded that both samples majorly have the α-crystal phase and β-phase in a less degree.…”
Section: Resultsmentioning
confidence: 92%